Not all fun and games: videogame labour, project-based workplaces, and the new citizenship at work - Milburn, Trudy (Journal of Broadcasting & Electronic Media, 2025)
Keywords: Citizenship; Engineering; Law; Political science; Public relations; Sociology; Work (physics); dept.aa

Social Media Faux Pas: Promoting individual or organizational expertise - Milburn, Trudy (Casing Organizational Communication, 2022)
Keywords: dept.aa

Communicating User Experience: Applying Local Strategies Research to Digital Media Design - Milburn, Trudy (2015)
Communicating User Experience illustrates how the use of Local Strategies Research (LSR) methodologies enables designers to understand the cultural implications for user actions and practices in a...
Keywords: dept.aa

Book Review: Culture 2.0: The Intersection of National and Organizational Culture and Unruly Speech: Displacement and the Politics of Transgression - Milburn, Trudy (Management Communication Quarterly, 2024)
Keywords: book review; dept.aa

Book Review: Robin James Smith, Richard Fitzgerald, and William Housley (eds), on Sacks: Methodology, materials, and inspirations - Milburn, Trudy A. (Discourse Studies, 2021)
Keywords: book.review; dept.aa

Coded communities: organizing boundless diversity - Milburn, Trudy A. (Annals of the International Communication Association, 2021)
Communication researchers have used speech codes theory to interpret local conduct. This qualitative meta-analysis draws upon twenty years of peer-reviewed journal articles and books (2000–2019) that specifically use the concept of speech community within research about speech codes. Although speech community is incorporated into one of the six main tenets of speech codes theory, the concept has not been used consistently. After reviewing how speech codes theory researchers use the concept of speech community, I draw comparisons between those who describe mediated and intercultural practices to interrogate the a priori assertion of a speech community. I conclude by arguing that one must understand the particular social relations among speakers before asserting the existence of a speech community. © 2021 International Communication Association.
Keywords: dept.aa; peer-reviewed; ⛔ No DOI found

Early college program implementation and growth: a collaborative initiative by a state university - Yavuz, Olcay; Milburn, Trudy (Concurrent Enrollment Review, 2025)
This article explores a collaborative initiative undertaken by a state university aimed at implementing and expanding an Early College Program. The conceptual framework, practical strategies, collaborative efforts and background of this initiative are presented. With a focus on improving college access for all, the article introduces the university's efforts to promote an inclusive Early College Program accessible to high-need students in particular. This collaborative approach highlights the importance of fostering collaboration among both internal and external partners of Institutions of Higher Education (IHE). By sharing insights into the program design and implementation, the article aims to inspire similar initiatives and contribute to the ongoing dialogue promoting early college experiences for all.
Keywords: Conceptual framework; Focus (optics); Focus group; Higher education; Program evaluation; State (computer science); dept.aa; dept.edl

Considering the moment: Workforce development for the faculty–administrator transition - Milburn, Trudy; Winchatz, Michaela (Communication Education, 2026)
Keywords: Higher education; Job training; Transition (genetics); Transition countries; Workforce; Workforce development; dept.aa

New England Town Meeting and the Cultivation of Deliberative Play - Townsend, Rebecca M.; Milburn, Trudy (American Behavioral Scientist, 2022)
Participants of New England town meeting must follow protocols to participate in this direct democratic process. Over the past 200 years, the protocols have been enacted and adapted by participants in small towns across the region. Within annual meetings, one can find small breaches that could be interpreted as playful acts. In this paper, we use the comic frame as a theoretical lens to interpret instances of such play within the rhetorical deliberation of one New England town meeting. We analyze two instances where speakers playfully use recognized parts of town meeting to achieve their rhetorical ends. We conclude with a discussion of the way play can help accomplish identification in public discourse.
Keywords: dept.aa; peer-reviewed

Translating Tasks for International Classrooms - Townsend, Rebecca M; Milburn, Trudy (Internationalizing the Communication Curriculum in an Age of Globalization, 2019)
This chapter presents a case study from an American university’s partnership with a Polish university. The case involves an assignment to international students studying for their master’s degrees: translating “key concepts in intercultural dialogue” for publication on the Center for Intercultural Dialogue’s website. There were several problems of translation of the task assignment. One problem is the translation of expectations. Learning outcomes occur for professors, too, and the chapter offers reflection on what lessons were realized for future teaching in the international classroom.
Keywords: dept.aa

Sword with a dual edge: Membership categorization and stereotyping in elite European club football commentary (chapter 12) - Hansen, Alan; Milburn, Trudy (Communicated Stereotypes at Work, 2024)
Communicated Stereotypes at Work highlights the pervasiveness and complexity of stereotypes in the workplace by analyzing the role they play in a variety of professional settings. Contributors exp...
Keywords: dept.aa

Organizational communication scholars and U.S. higher education leadership: opportunities and challenges when scholars become administrators - Castor, Theresa; Milburn, Trudy; Eisenberg, Eric M.; Shockley-Zalabak, Pam (Management Communication Quarterly, 2025)
Universities and colleges are organizations that significantly impact students, their communities, and society. This forum explores how organizational communication scholars who are university leaders have applied their scholarly backgrounds to inform their roles. The forum participants engage in the work of being reflective practitioners to shed light on how organizational communication theory can help in negotiating the everyday lived experience of academic leadership. Three key issues are explored: (1) in what ways are organizational communication scholars uniquely positioned to assume a university leadership role? (2) how do communication concepts inform the communication practices of administrators? and (3) how do communication practices contribute to universities as multi-faceted institutions? The participants conclude by reflecting on current challenges in higher education and the potential of organizational communication scholars to play a vital role in navigating those challenges.
Keywords: dept.aa; peer-reviewed